2020
DOI: 10.1002/rra.3662
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the potential to restore the multi‐functionality of floodplain systems by considering ecosystem service quality, quantity and trade‐offs

Abstract: River floodplains are hotspots of productivity and biodiversity and recognized to fulfil vital ecosystem functions and services. Restoration measures of the decoupled Danube floodplains east of Vienna aim to re‐establish multi‐functionality, that is, ensure navigation, preserve and restore unique fluvial and riparian habitats and re‐establish natural processes and service provisioning. Side‐channels are proposed for reconnection combined with the removal of embankments and groins. We evaluated how a programme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The high degree of biodiversity and level of primary productivity of floodplains exceed the production of either purely terrestrial or aquatic ecosystems (Tockner and Stanford, 2002). The dynamics and naturally high biodiversity of floodplains are responsible for their high multifunctionality (Meli et al, 2014;Funk et al, 2020). Focusing on the value of global ecosystem services, Costanza et al (1997) found that floodplains are the second best ranked ecosystem type, behind estuaries, in terms of their per hectare value to society.…”
Section: The Ecosystem Functions and Services Of A Floodplainmentioning
confidence: 99%
“…The high degree of biodiversity and level of primary productivity of floodplains exceed the production of either purely terrestrial or aquatic ecosystems (Tockner and Stanford, 2002). The dynamics and naturally high biodiversity of floodplains are responsible for their high multifunctionality (Meli et al, 2014;Funk et al, 2020). Focusing on the value of global ecosystem services, Costanza et al (1997) found that floodplains are the second best ranked ecosystem type, behind estuaries, in terms of their per hectare value to society.…”
Section: The Ecosystem Functions and Services Of A Floodplainmentioning
confidence: 99%
“…Their study reveals trade‐offs between agricultural food production (provisioning ES) and most regulating and cultural ES, whereby the latter were positively affected by a low amount of arable land in the catchment and a large active floodplain area. Likewise, Funk et al (2021) observed strong synergies between regulating ES (biodiversity, nutrient retention) and specific cultural ES on a Danube floodplain east of Vienna. Trade‐offs existed between but also within ES categories, for example, between stagnotopic and rheotopic communities.…”
Section: Themes Of This Special Issuementioning
confidence: 96%
“…While there are several frameworks according to which landscape-level decisions could be made (optimization, e.g. according to pareto-optimal combinations of ES- Vallet et al 2018), within the ES-related topics, it is often multifunctionality that is promoted as the best solution (Sanon et al 2012;Funk et al 2020). Sensitive and protected areas might however not always be outstanding in terms of multifunctionality.…”
Section: Integrated Valuation Of Freshwater Ecosystem Servicesmentioning
confidence: 99%
“…For example, reviews on riverine ES found only 69-89 studies across the past years (Hanna et al 2018;Kaval 2019), and 1026 studies for lake and wetland ES together (Xu et al 2018), while Reynaud and Lanzanova (2017) found 133 studies focusing solely on lake economic valuation. A systematic review on the assessment and conservation management in large floodplain rivers revealed that only 1.6% of the studies addressed ES , even though considering ES can be highly relevant when assessing the effects of river restoration as shown in the recent study by Funk et al (2020). On the other hand, a review of * 3.000 publications showed that many papers on ES were published in general environmental journals, or specific sectoral journals (forestry, agriculture, etc.…”
Section: Introductionmentioning
confidence: 99%